Empirical estimation of risk-neutral density from option prices - Bahaludin, Hafizah; Abdullah, Mimi Hafizah (2016)
The objective of this study is to extract the forward looking information that is embedded in option prices namely the risk-neutral density (RND). The smoothing volatility function approach is widely used by applying the proper interpolation in RND estimation. This paper presents the statistical comparison of interpolation techniques between the second and fourth order polynomials in the calculation of RND. The RNDs are extracted from the Dow Jones Industrial Average (DJIA) index options that focus on options with a one month constant maturity. The empirical evidence shows that the interpolations of second and fourth order polynomials provide a statistical difference in RND estimation. The fourth order polynomial is the best interpolation model which yields the lowest mean square error.